PEMBERIAN UPAH PEMOTONGAN HEWAN QURBAN MENURUT HUKUM ISLAM (Studi Pada Masyarakat Tanjung Barulak Kab. Tanah Datar) - Hendri Hendri; Andriyaldi Andriyaldi (Alhurriyah, 2018)
Every year Muslims commemorate the feast of Idhul Adha. One form of celebration is done by sacrificing. Sacrifice is an amaliyah service whose provisions are regulated in Islam. Sacrifice according to etymology comes from Arabic, namely qaraba which means close. The word qurban is commensurate with the word al-udhiyyat which is defined as the name of an animal slaughtered on the Idhul Adha feast day and tasyrik days to draw closer to Allah. Whereas the term sacrifice means the slaughter of certain animals with the intention of drawing closer to Allah SWT, which is performed on the feast of Idhul Adha or in the days of Tasyrik which is the 11th, 12th and 13th of Dhulhijah. However, in Indonesia the implementation of slaughtering sacrificial animals in each region is carried out differently. Especially giving wages for slaughtering sacrificial animals. This article uses the analytical content method for the syllables' arguments and also uses the field research method, which is to gather information in the field related to the wages of slaughtering sacrificial animal sacrifices that occur in the middle of the community, especially the Tanjung Barulak district. Tanah Datar. The implementation of slaughtering sacrificial animals in the middle of the community is carried out differently. This is because this is a tradition that has been passed down for generations, both wages given in the form of meat, head, feet or parts of sacrificial animals are a reward for people who cut or clean sacrificial animals. The wages were still given but did not take from the sacrificial animal and then replaced the wages in the form of money taken or requested and collected from the sacrificial participants.